2017
DOI: 10.1289/ehp1521
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metal Concentrations and Incident Coronary Heart Disease in Chinese Adults: The Dongfeng-Tongji Cohort

Abstract: Background:Circulating metals from both the natural environment and pollution have been linked to cardiovascular disease. However, few prospective studies have investigated the associations between exposure to multiple metals and incident coronary heart disease (CHD).Objectives:We conducted a nested case–control study in the prospective Dongfeng-Tongji cohort, to investigate the prospective association between plasma metal concentrations and incident CHD.Methods:A total of 1,621 incident CHD cases and 1,621 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 49 publications
4
67
1
Order By: Relevance
“…The methodological quality of the studies was also assessed and those with missing data on, or incomplete definitions of, the study design, population, exposure condition, or outcome variables were excluded [42][43][44][45][46][47][48][49]. Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51]. In addition, as there was only one study analysing each of soluble E-selectin, myeloperoxidase, plasminogen activator inhibitor-1 (PAI-1), soluble Intercellular Adhesion Molecule 1 (ICAM-1) and soluble Vascular cell adhesion protein 1 (VCAM-1) [18], carotid atherosclerosis indices (CAIs) [52], common carotid intima media thickness, plaque score and the presence of plaque in the common carotid [53], peripheral vascular disease [54,55] as well as some other CVD subtypes and clinic markers [21,27,[56][57][58][59][60][61], respectively, these variables have not been included in our dose-response meta-analysis.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The methodological quality of the studies was also assessed and those with missing data on, or incomplete definitions of, the study design, population, exposure condition, or outcome variables were excluded [42][43][44][45][46][47][48][49]. Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51]. In addition, as there was only one study analysing each of soluble E-selectin, myeloperoxidase, plasminogen activator inhibitor-1 (PAI-1), soluble Intercellular Adhesion Molecule 1 (ICAM-1) and soluble Vascular cell adhesion protein 1 (VCAM-1) [18], carotid atherosclerosis indices (CAIs) [52], common carotid intima media thickness, plaque score and the presence of plaque in the common carotid [53], peripheral vascular disease [54,55] as well as some other CVD subtypes and clinic markers [21,27,[56][57][58][59][60][61], respectively, these variables have not been included in our dose-response meta-analysis.…”
Section: Data Sourcesmentioning
confidence: 99%
“…In contrast, an American study based on the Normative Aging Study cohort reported an increased incidence of coronary heart disease [Hazard ratio = 1.73 (95% CI: 1.05, 2.87)] among individuals with B-Pb ≥50 lg=L vs. <50 lg=L, even after adjustment for risk factors and confounders (Jain et al 2007). Finally, a study in Chinese adults reported no significant trend between plasma lead levels and incident coronary heart disease using plasma lead modeled by quartiles (Yuan et al 2017), but plasma lead is rarely used as a biomarker for lead exposure. The level of lead in plasma is usually <1% of that in whole blood and the plasma levels in the study by Yuan et al (2017) were much higher than what can be expected in a population study (Hernández-Avila et al 1998;Skerfving and Bergdahl 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Finally, a study in Chinese adults reported no significant trend between plasma lead levels and incident coronary heart disease using plasma lead modeled by quartiles (Yuan et al 2017), but plasma lead is rarely used as a biomarker for lead exposure. The level of lead in plasma is usually <1% of that in whole blood and the plasma levels in the study by Yuan et al (2017) were much higher than what can be expected in a population study (Hernández-Avila et al 1998;Skerfving and Bergdahl 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many biological matrixes such as urine, plasma, and whole blood have been used to appraise different metals' exposure levels. For example, urine has been proposed as the best matrix for representing the long term exposure levels of arsenic and cadmium while whole blood is an appropriate matrix for characterizing iron exposure [29,30]. Compared with other biological matrixes, noninvasive urine samples are easy-to-access thus used more frequently in large-scale epidemiological studies.…”
Section: Covariate Data Collectionmentioning
confidence: 99%
“…However, due to the variability of urinary metals, a single urine sample might lead to exposure misclassi cation [31]. Considering these aspects, we selected urinary vanadium, cobalt, arsenic, and selenium in the primary analyses according to our laboratory's previous experiments and the two principles: a) metals' concentrations in urine have signi cant correlations (p correlation < 0.05) with those in whole blood and plasma; b) fair to good reproducibility (intra-class correlation coe cient > 0.40) in repeated urine samples (Supplementary Table S1) [30,32]. Statistical results about the rest of 16 metals were represented in Supplementary Materials.…”
Section: Covariate Data Collectionmentioning
confidence: 99%